Subpopulations of swine γδ T cells defined by TCRγ and WC1 gene expression. (December 2021) - Le Page, Lauren; Gillespie, Alexandria; Schwartz, John C.; Prawits, Lisa-Maria; Schlerka, Angela; Farrell, Colin P.; Hammond, John A.; Baldwin, Cynthia L.; Telfer, Janice C.; Hammer, Sabine E.
Abstract: γδ T cells constitute a major portion of lymphocytes in the blood of both ruminants and swine. Subpopulations of swine γδ T cells have been distinguished by CD2 and CD8α expression. However, it was not clear if they have distinct expression profiles of their T-cell receptor (TCR) or WC1 genes. Identifying receptor expression will contribute to understanding the functional differences between these subpopulations and their contributions to immune protection. Here, we annotated three genomic assemblies of the swine TCRγ gene locus finding four gene cassettes containing C, J and V genes, although some haplotypes carried a null TRGC gene (TRGC4). Genes in the TRGC1 cassette were homologs of bovine TRGC5 cassette while the others were not homologous to bovine genes. Here we evaluated three principal populations of γδ T cells (CD2 + /SWC5 -, CD2 - /SWC5 +, and CD2 - /SWC5 - ). Both CD2 − subpopulations transcribed WC1 co-receptor genes, albeit with different patterns of gene expression but CD2 + cells did not. All subpopulations transcribed TCR genes from all four cassettes, although there were differences in expression levels. Finally, the CD2 + and CD2 − γδ T-cell populations differed in their representation in various organs and tissues, presumably at least partially reflective of different ligand specificities for their receptors. Highlights: By fully annotating three genomic assemblies of the swine TRG gene locus, we found genes in the porcine TRGC1 cassette were homologs of the bovine TRGC5 cassette. CD2 + and CD2 − γδ T cells differed by tissue distribution and TRG and WC1 gene usage. Porcine CD2 + SWC5 - γδ T cells showed no expression of TCR co-receptor WC1 genes. SWC5 profile depended differential expression of WC1 genes in CD2 − γδ T cells. Distribution of swine γδ T cell subsets is partially reflective of different ligand specificities for their receptors.